Analysis of groups' multi-day leisure travel behaviors. (20th October 2022) - Shi, Jing; Long, Yuxi; Xin, Lei
Abstract: The purpose of this paper is to study the behavior characteristics and spatiotemporal distribution of groups' multi-day leisure travel, and to quantify the impact of the elderly and children on group travel choices. Based on questionnaire and social media data, three choice models and an agent-based simulation model were established to explore the micro-choice behavior characteristics and the macro-spatiotemporal distribution of groups' multi-day leisure travel by arranging the travel rules and by simulating the route of travel groups. The results of data analysis and simulation indicate that: (1) Travel groups with the elderly or children are less affected by the high-speed railway network and prefer self-driving traveling. (2) Groups with the elderly or children tend to travel for more days and visit more cities, while groups without the elderly or children pursue high-quality tourism resources. (3) High-quality tourist attractions bring more tourists to nearby tourist attractions, promoting regional tourism cooperation.